On the non universality of surface density of galaxies - Del Popolo, A. (Advances in Astronomy and Space Physics, 2012)
We studied the correlation between the central surface density of dark matter haloes and the halo core radius of galaxy and galaxy recently studied on a wide range of scales. For this aim we used the secondary infall model, that we previously published, to get the halo density profile taking into account the effect of ordered and random angular momentum, dynamical friction, and adiabatic contraction of the dark matter due to the baryons collapse. We found that the column density within the halo characteristic radius r ͙ is not a universal quantity as claimed by other authors, but it correlates with the halo mass M₂₀₀. The scatter in the slope of the S − M relation is 0.16 ± 0.05, leaving small room for the possibility of a constant surface density.